The Solomon curse [large type] - Cussler, Clive; Blake, Russell (Cussler, Clive. Fargo adventures., 2015)
Some say the bay off Guadalcanal in the Solomon Islands was the site of the lost empire of the Solomon king, and that great treasure lies beneath the waters. Others say terrible things happened here, atrocities and disappearances at the hands of cannibal giants, and those who venture there do not return. So how can Sam and Remi Fargo resist? Clues and whispers lead them on a hunt from the Solomons to Australia to Japan, and what they find at the end of the trail is both wonderful and monstrous-- and like nothing they have ever seen before.